Effects of different sources of dietary chromium on meat quality and amino acid content of broilers - TANG Lihua; FANG Rejun; ZHOU Rushun; ZHANG Kai; HU Longchang (浙江大学学报. 农业与生命科学版, 2013)
Chromium as a beneficial element was occasionally indicated by more and more investigations reported. Trivalent chromium Cr (Ⅲ) has been accepted as an essential element for 30 years which can affect the growth performance, carcass characteristics, pork quality, reproduction and tissue deposition of domestic animals that were fed with Cr (Ⅲ) supplementation in diet through changes protein, nucleic acid and lipid metabolism. Chromium is found in GTF-like forms in the livers of mammals given inorganic chromium, but this could reflect the manifold effects of insulin rather than further biochemical roles for chromium. Moreover some other reports indicated Cr (Ⅲ) appeared not to be an essential element, and its potential effects on domestic animals might be considered pharmacological. Limited research is available for addressing the effect of Cr on meat quality of broiler elucidated by determining the fiber muscle density, total antioxidant capacity and amino acid content. Thus, the purpose of present experiment was to evaluate the effects of three different sources of chromium (yeast chromium, chromium picolinate and methionine chromium) on meat quality and amino acid content of Arbor Acres (AA) broilers.Seven hundred and ninety-two one-day-old Arbor Acres broilers were randomly allocated to six dietary treatments. Each treatment had four replicates (cages) with thirty three broilers per cage, respectively. The dietary treatments were: 1) corn-soybean meal basal (B: according to NRC, 1994), 2) B+0.2 mg/kg of Cr (as yeast chromium), 3) B+0.2 mg/kg of Cr (as chromium picolinate),4) B+0.1 mg/kg (as methionine chromium; Ⅰ), 5) B+0.2 mg/kg (as methionine chromium; Ⅱ), 6) B+0.6 mg/kg of Cr (as methionine chromium; Ⅲ). The fiber density, fiber areas and its antioxidant index of leg muscle, as well as amino acids content of muscle were determined.The results showed that the fiber density of breast muscle and fiber areas of leg muscle were reduced (P<0.05) in broilers fed with yeast chromium diets, fiber density of breast muscle was reduced (P<0.05) in broilers fed with methionine chromium (Ⅱ) diets, fiber areas of breast muscle and leg muscle were reduced (P<0.05) in broilers fed with methionine chromium (Ⅰ) diets compared with broilers fed with the control diets. Protein content of breast muscle was reduced (P<0.05) in broilers fed with chromium picolinate diets, and fat content of breast muscle was reduced (P<0.05) in broilers fed with methionine chromium (Ⅱ) diets. Antioxidant index of breast muscle and leg muscle were not affected (P> 0.05) by treatments, with the exception that, total antioxidant capacity (T-AOC) of leg muscle from broilers fed with methionine chromium (Ⅱ), total antioxidant capacity (T-AOC) of breast muscle and catalase (CAT) of leg muscle from broilers fed with methionine chromium (Ⅲ), all of these had an increased (P<0.05) than broilers fed with the control diets. Main amino acids of muscle were not affected (P>0.05) among treatments, with the exception that the alanine content of breast muscle in broilers fed with chromium picolinate reduced (P<0.05) compared with that of broilers fed with the control diets.These suggested that dietary supplementation of yeast chromium or methionine chromium in broilers had a significant effect on muscular tissue structure and oxidation resistance of muscle; however, the main amino acids of muscle were not affected by treatments.